The link between neutrophils, neutrophil extracellular traps, and NLRP3 inflammasomes: The dual effect of CD177 and its therapeutic potential in acute respiratory distress syndrome/acute lung injury - Jingying Li; Zhansheng Fang; Shumin Xu; Haiwei Rao; Junzhe Liu; Kunjian Lei; Lufei Yang; Chong Wang; Zhenguo Zeng (Biomolecules & Biomedicine, 2024)
Neutrophils are important inflammatory effector cells that protect against foreign invasion but also cause self-harm. Numerous neutrophils infiltrate the lungs in acute respiratory distress syndrome/acute lung injury (ARDS/ALI) patients. However, the exact impact of neutrophil infiltration on ARDS's onset and progression remains unclear. To investigate this, we analyzed two ARDS-related datasets from the Gene Expression Omnibus public database and discovered an association between CD177, a neutrophil-specific surface protein, and ARDS progression. We used quantitative flow cytometry to assess CD177+ neutrophils in the peripheral blood of clinical ARDS patients versus healthy controls, finding a significant increase in CD177+ neutrophils percentage among total neutrophils in ARDS patients. This finding was further confirmed in ALI mouse models. Subsequent animal experiments showed that anti-CD177 effectively reduces pulmonary edema, neutrophil infiltration, and inflammatory cytokine release, along with a decrease in reactive oxygen species (ROS) and myeloperoxidase (MPO) levels. We also established an in vitro co-culture system to mimic neutrophil and lung epithelial cell interactions. In the anti-CD177 group, we observed decreased expression of NLRP3, caspase 1, PAD4, MPO, and ROS, along with a reduction in certain inflammatory cytokines. These results indicate a crucial role for the CD177 gene in ARDS's development and progression. Inhibiting CD177 may help mitigate excessive activation of NLRP3 inflammasomes, ROS, and neutrophil extracellular traps (NETs), thus alleviating ARDS.